Studi perbandingan profil asam lemak minyak ikan lele dan minyak ikan keting melalui pemurnian dengan bentonit - Jannah, Nadia Miftahul; Ningrum, Karina Primatyas (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
In general, fish have high omega-3 and omega-9 fatty acid content and are beneficial for health. This makes fish oil develop into a food supplement. Increasing the amount of free fatty acids in oil can potentially reduce the quality and damage of fish oil. Adsorbents have bleaching properties that can affect color changes in fish oil and fish oil content. This study aims to determine the effect of bentonite adsorbent treatment on the fatty acid profile of catfish oil and keting fish oil analyzed using the Gas Chromatography Mass Spectrometry (GC-MS) method. Catfish oil (CFO) and Keting fish oil (KFO) samples were extracted without using organic solvents and then treated with bentonite as an adsorbent. The extracted oil was derivatized and then injected into the GC-MS instrument system. There were 29 types of fatty acids detected in each sample, namely 12 types of saturated fatty acids (SFA), 8 types of monounsaturated fatty acids (MUFA), and 9 types of double unsaturated fatty acids (PUFA). The effect of purification with bentonite was analyzed using One-way ANOVA from Minitab19 software showing that there were differences in the content of fatty acid profiles of CFO and KFO that were purified and not purified with bentonite, shown in each category of fatty acids SFA, MUFA and PUFA which had a p value <0.05.